Medieval Roots of the European Union - Dublikash, Tatiana (Ukrainian Sociological Journal, 2019)
The article is devoted to the comparative historical analysis of modern and medieval Euro-integration processes. Particular attention is paid to the role of France and Germany in the integration project of the European Union. The author analyzes both the socio-political processes that unfolded in Europe in the 9th and 10th centuries before and after the division of the Frankish empire, and the current state of the European Union. The comparison was implemented in three selected areas of foreign and domestic policy of the Frankish empire: military colonization and integration by the Franks of East Rhine Germany into the state of the Franks, the Saxon wars and the campaigns against the Slavs. In the context of modern socio-political processes in the European Union, the tendencies that were observed already in the Middle Ages are highlighted; the connection between them is shown. Characterized by the features of the East Frankish Kingdom, Western and Middle, the balance of forces between them compared with the peculiarities of the role of modern Germany, France and Italy in the project of the European Union. The political preferences of the disputed region of Alsace-Lorraine are analyzed in the context of the long-term historical competition of France and Germany for these territories. The strategy of enlargement of the European Union and, in particular, the Eastern Partnership program, is rethought through the prism of the principles of foreign policy of the Holy Roman Empire of the German nation. In particular, the role of the so-called brands, fortified borders, which acted as military borders, was analyzed. Based on the identified trends, a forecast of the future of the European Union for the coming decades has been done. The assessment of the prospects of full membership of Albania, Bosnia and Herzegovina, Kosovo, Macedonia, Montenegro, Serbia, Moldova, Ukraine and Georgia in the EU is given. Вased on the provisions of string theory the theoretical understanding of the sustainability of long-term and repeatability of short-term socio-political trends is carried out .